Herbal medicine in pregnancy - mahdieh jaafari (Advanced Herbal Medicine, 2017)
Background and aims: Herbal medicines are derived from natural plants with medicinal or preventive properties. Use of herbal remedies has increased despite lack of scientific evidence about their efficacy and safety during pregnancy. Methods: This is an internet-based study. In this mini review, a publication search was conducted in the Medline, Google Scholar, and EMBASE databases, using a combination of medical subject headings (MeSH) and Black cohosh, Ginseng, Red Raspberry, Aloe vera, Chamomile, Chasteberry and Garlic keywords. The MeSH terms included herbal medicine, herbal products, pregnancy, and pregnant women. Results: Herbal remedies are very common. Some information will list an herb as safe to consume during pregnancy, whereas another source may list the same herb as unsafe depending on the source. Although herbs are natural, not all herbs are safe to take during pregnancy. Conclusion: Medicinal herbs can be very useful and effective during pregnancy. Despite the beneficial effects of herbs during pregnancy, use of certain herbal and traditional medicines without prior consultation with a health care professional may be harmful for pregnant women and their babies.